The Financial Manager: Basic Aspects of Financial Administration. - Barrett, William B. (The Accounting Review, 1967)
Reviews the book "The Financial Manager: Basic Aspects of Financial Administration," by Jerome B. Cohen and Sidney M. Robbins.